Assessment of Selected Groundwater Quality Parameters in the Suknah area and Their Relationship to Geological Formations Using Geographic Information Systems (GIS) and Their Role in Supporting Sustainable Development - نبيل صالح علي عمر; امحمد صالح عبد الهادي خليفة (African Journal of Advanced Pure and Applied Sciences, 2026)
This study was carried out in the Suknah area of Jufra Municipality with the aim of assessing the qualitative characteristics of groundwater and evaluating their suitability for domestic, agricultural, and industrial purposes. The study also examined the relationship between these characteristics and the prevailing geological formations using Geographic Information Systems (GIS). Spatial distribution maps for the key groundwater quality parameters were generated through GIS analysis. Nine groundwater samples were collected from wells within the study area. The sampling sites were selected in a representative manner based on hydrogeological characteristics and the spatial distribution of geological formations. The measured parameters included pH, electrical conductivity (EC), total dissolved solids (TDS), chloride (Cl⁻), and bicarbonate (HCO₃⁻) .GIS interpolation (IDW) was used to generate spatial maps. The results indicate that most wells contain water with highly salinity, with salinity levels exceeding the permissible limits set by both Libyan standards and World Health Organization guidelines. Consequently, the groundwater is unsuitable for drinking and various industrial uses, but remains suitable for irrigating high-salinity-tolerant crops. The findings further reveal that the dominant geological formations, particularly limestone and gypsum, significantly influence the concentrations of dissolved salts in the groundwater. The study provides essential spatial data that can support sustainable water-resource management in the region.